1999
DOI: 10.1111/1468-0432.00077
|View full text |Cite
|
Sign up to set email alerts
|

Organizing Sexualities, Organized Inequalities: Lesbians and Gay Men in Public Service Occupations

Abstract: This article examines the experiences of lesbians and gay men who are employed in a variety of public service occupations in the UK, drawing upon interview material gathered during a broader research project on lesbian and gay self-organization within the public sector trade union UNISON. It forges pathways through hitherto unexplored territories by concentrating upon career trajectories beyond the closet, arguing that those who dare to come out and proud in public sector workplaces will tread a precarious tig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(111 citation statements)
references
References 20 publications
2
109
0
Order By: Relevance
“…The demarcation between one's sexual identity and her/his work and professional identity, and the subsequent denial of one to the other, has been assimilated to inhabiting two worlds (Humphrey, 1999). Some LGBTs, in fact, create a façade of conformity with colleagues and managers often constructing a heterosexual partner and a heterosexual life (Özbilgin & Woodward, 2003;Ward & Winstanley, 2003), suppressing the sense of who they are.…”
Section: Compulsory Heterosexuality: Understanding Heteronormativity mentioning
confidence: 99%
“…The demarcation between one's sexual identity and her/his work and professional identity, and the subsequent denial of one to the other, has been assimilated to inhabiting two worlds (Humphrey, 1999). Some LGBTs, in fact, create a façade of conformity with colleagues and managers often constructing a heterosexual partner and a heterosexual life (Özbilgin & Woodward, 2003;Ward & Winstanley, 2003), suppressing the sense of who they are.…”
Section: Compulsory Heterosexuality: Understanding Heteronormativity mentioning
confidence: 99%
“…Researchers (Humphrey 1999;Schneider 1986) have also found that many homosexuals are fired when their sexual orientation is discovered. In terms of the hiring process, homosexuality, at least initially, may not play as a large factor as actual on the job training or work (Benokraitis and Feagin 1995;Levitt and Klassen 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Bernstein and Kostelac (2002), who studied police officers, found that one-fourth of their sample "felt that recruiting homosexual officers undermines department morale" (p. 316). Furthermore, studies have suggested that many lesbians and gay men anticipate discrimination, however, a smaller percentage of gay men and lesbians actually experience discrimination in their workplace (Bell and Weinberg 1978;Humphrey 1999;Levine and Leonard 1984;Saghir and Robins 1973;Schneider 1986;Taylor and Raeburn 1995). Other researchers noted that, in some cases, gay men and lesbians must pass as heterosexuals in order to gain access to the job market (Badgett et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…LGBT equalities work was framed as part of professional norms and duties, an ethic of public service and care that is typically associated with public sector organizations (Humphrey 1999), regardless of a person's private beliefs. Related to this it was also, in part, about the management of prejudice through privatising it.…”
Section: Privatisationmentioning
confidence: 99%